Antibacterial effect of Aloe Vera on Bacteria Isolated from Cases of Wound Infection - Naik, Vaishnavi Vishram; Rao, Pooja; Suman, Ethel; Jeppu, Udayalaxmi (Infectious Disorders - Drug Targets, 2025)
BackgroundAntimicrobial resistance exhibited by bacteria against the majority of antibiotics has resulted in research on alternative methods of treatment. Aloe vera has a strong tradition as a medical plant with a wide range of therapeutic uses.ObjectiveThe objective of this study is to determine the antibacterial activity of gel and crude ethanol leaf extract of Aloe vera against Staphylococcus aureus and Enterobacterales isolated from wound infections.MethodsIt is a cross-sectional study conducted over a period of 7 months. Antibacterial effect of the ethanol leaf extract and gel was determined by the punch well method. Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of the ethanol leaf extract were determined by macro broth dilution technique.ResultsAloe vera ethanol leaf extract induced a mean zone size of 13.0 ± 6.0 mm and 16.7 ± 8.4 mm, respectively, for S. aureus and Enterobacterales by Punch Well method (p≤0.002). Whereas Aloe vera gel failed to induce any zone of inhibition for all the isolates p<0.001. Mean MIC of Aloe vera leaf extract against 74 S. aureus was 94 ± 41.23 mg/ml and against 73 Enterobacterales, it was 45.6 ± 20 mg/ml p < 0.001. Mean MBC of Aloe vera leaf extract against 74 S.aureus isolates was 188 ± 82.46 mg/ml and against 73 Enterobacterales was 91.18±40 mg/ml p < 0.001.ConclusionAloe vera ethanol leaf extract showed a good antibacterial effect against the different strains of bacteria causing wound infection. The present article shows the possibility of future use of natural products for the treatment of wound infections.
Keywords: Plant extract